ANCA-Associated Vasculitis in Latin America: A Systematic Literature Review. Issue 1 (January 2022) - Pimentel-Quiroz, Victor R.; Sattui, Sebastian E.; Ugarte-Gil, Manuel F.; Alarcón, Graciela S.
Abstract : Abstract: Most of the existing literature, including epidemiological studies and clinical trials, on antineutrophil cytoplasmic antibodies (ANCA)–associated vasculitis (AAV) include North American (mainly United States and Canada), European, and Asian populations. Few studies have focused on multiethnic populations such as the one from Latin America. Racial and ethnic differences in the incidence of AAV could partially explain the comparatively low number of AAV studies originating in Latin America. However, given the racial/ethnic diversity as well as socioeconomic differences existing in this region, better reporting of AAV presentations and outcomes in Latin America could highlight valuable gaps on the understanding and treatment of these patients. Recently, larger case series and studies have provided better clinical information regarding AAV patients in Latin American countries; however, further information is needed to address gaps such as risk factors, genetic profiles, clinical features, and predictors of clinical outcomes. For these reasons, we have performed a systematic literature review to enhance our understanding of AAV patients in Latin America. We have included 11 articles focused on the epidemiological and clinical features of AAV in Latin America; some similarities and differences with AAV in other regions are shown in these articles. We have identified differences in their prevalence across Latin American countries, which may reflect reporting bias or true ethnic differences among the countries. Our findings should encourage further investigation into AAV in Latin America; such studies will hopefully lead to the optimal management of these patients. Abstract : Supplemental digital content is available in the text.